FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA AKUNTAN PUBLIK DI JAKARTA - SUGIARTO PRAJITNO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
This study aims to obtain empirical evidence about the effect of audit structure, role conflict, role ambiguity, understanding of good governance, task complexity and organizational culture on auditors’ performance. Object of this study is the auditors who work in public accounting firms in Jakarta 2012 period. The selection of sample using purposive sampling method. The number of questionnaires distributed was 157 copies, but only 145 questionnaires returned 115 questionnaires and meet the criteria to be used as the sample for this study. Analysis of the data in this study using multiple regression analysis. The results of this study indicate that the understanding of good governance, the structure of the audit, role conflict, role ambiguity, understanding of good governance, and task complexity do not have a significant effect on auditors’ performance and the only organizational culture has a significant influence on auditors’ performance.